2020
DOI: 10.21153/jtlge2020vol11no1art886
|View full text |Cite
|
Sign up to set email alerts
|

Future-proofing accounting professionals: Ensuring graduate employability and future readiness

Abstract: Key global and Australasian bodies have reported research suggesting the accounting profession is one of the most vulnerable to disruption through automation and changed business models. For universities seeking to improve the employability of graduates and professional bodies seeking to support professional members on a successful lifelong career, the research presented in this paper reconfirmed the need to reappraise the capabilities that would enhance professional practice and lead to sustained careers. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The study signals an important opportunity for university providers, employers and professional associations to identify ways, ideally in partnership, to better develop technology-related skills among aspiring and current ECAs. Importantly, enhancing digital capability among ECAs is critical for their own career sustainability (Bowles et al , 2020) and for the success of organisations and the profession more broadly (CPA Australia, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The study signals an important opportunity for university providers, employers and professional associations to identify ways, ideally in partnership, to better develop technology-related skills among aspiring and current ECAs. Importantly, enhancing digital capability among ECAs is critical for their own career sustainability (Bowles et al , 2020) and for the success of organisations and the profession more broadly (CPA Australia, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Despite suggestions that the accounting profession is one of the most vulnerable to disruption through automation and changed business models, Bowles et al (2020) report 24 capabilities, including six requirements considered essential for every professional seeking to work in accounting, finance, and related work roles. The findings provide evidence that these capabilities, in contrast to other reports suggesting that employment opportunities for accounting graduates are in decline, can create opportunities for sustainable careers.…”
Section: The 4ir and Its Impact On The Accounting Professionmentioning
confidence: 99%
“…It has analyzed that the extent to which an auditor's competencies can help in successful implementation of the e-audit system (AZIZOVA and Hakan, 2020;Supriadi et al, 2019). There is a surge in demand for advanced IT skills among accounting professionals (Bowles et al, 2020;Pan and Seow, 2016). IT showed that team problem-solving ability and computer audit activity positively influence internal audit performance, and that competencies indirectly influence internal audit performance through the mediating effects of team problem-solving ability and computer audit activity (Siew et al, 2020;Wu et al, 2017).…”
Section: Information Communication Technology Competencymentioning
confidence: 99%